Market Demand for Electric Vehicles under Technology Improvements and Tax Relief. Issue 8 (20th June 2020) - Gong, Bengang; Wang, Jiali; Cheng, Jinshi
ABSTRACT: This study aims to find ways to promote the demand for and acceptance of electric vehicles (EVs) by studying the impacts of two policies: tax relief and technology improvements. We find a balanced relationship between the two policies, causing low-carbon awareness to have the same effect on EV demand. Outside of equilibrium, greater low-carbon awareness, rather than price discounts or improved technology, can help improve demand. Furthermore, higher production inputs improve the EV technology level, but changes in the ratio of technology to cost affect customers' willingness to pay for EV products. Thus, technology and low-carbon awareness affect EV demand.